The Effect of Mudharabah Financing on Profitability at PT. Bank Sulselbar Syariah Makassar Branch - Andi Muhammad Al-Ayyubi, Andi Muhammad Al-Ayyubi; Muh. Rizal S; Jamaluddin; Nurhasni Muis (Fakultas Ilmu Sosial dan Hukum, 2025)
This research examines the effect of Mudharabah financing on profitability at PT. Bank Sulselbar Syariah Makassar Branch. The main purpose of this study is to determine how far Mudharabah financing contributes to increasing the bank’s profitability. This study uses a quantitative approach to measure the relationship between variables more objectively. The research was conducted at PT. Bank Sulselbar Syariah Makassar Branch from April to May 2023. The sample in this study consisted of 45 respondents who were selected based on the required criteria to represent the research population. The data collection techniques used were observation, questionnaires, and documentation to obtain both primary and secondary data. The analysis techniques applied include validity tests, reliability tests, normality tests, descriptive analysis, simple linear regression analysis, correlation coefficient analysis, and coefficient of determination analysis. The results of the study show that the indicators used for each variable demonstrate that the level of Mudharabah financing falls into the very good category, indicating effective financing management. Likewise, the profitability level of PT. Bank Sulselbar Syariah Makassar Branch is also in the very good category, reflecting optimal financial performance. Based on the coefficient of determination test, the influence between the two variables is categorized as strong or high. Therefore, it can be concluded that the influence of Mudharabah financing on profitability at PT. Bank Sulselbar Syariah Makassar Branch is very strong and significant.